PENINGKATAN PENGELOLAAN BANK SAMPAH TERATAI DI KELURAHAN NGADIREJO KOTA KEDIRI: - Ratnani Nurhayatie; Moh. Irmawan Jauhari (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2024)
The Purpose of this service activity can help the community in managing waste bank, solve problems, and increase the community's economy in a more independent manner, while encouraging the community to actively create 3R (Reduce, Reuse, Recycle) culture. The method used is community development with the principles of enabling, empowering and protecting. Where enabling creates a productive and constructive situation so that society can develop. Empowering focuses on strengthening potential value in society. Protecting focuses on protecting marginalized communities. The results of the service stated that the management of the Teratai Waste Bank, Ngadirejo Village, Kediri City, had become more organized, the people of Ngadirejo Village realized the importance of household-based waste management as well as its utilization, and integrated and coordinated waste management had a positive impact on the environment and the family economy.